"Hic": bir yokluk Romanı = Nothing: a novel of nonentity - Kayadibi, Saim (ikinci adam yayinlari, 2018)
The novel, in your hand, is one of the most needed novels for the modern man. It's about a story of a young man who does not find answers to his questions inside. He decided to come to Malaysia with the influence of his Malaysian friends he met in England. Then his new friends, whom he met in Malaysia, draw him to the doors of a different world. At this door, the keys that will take the young man to eternity are hidden. Hodja Ferhun, whom he met by chance through his friends, makes complete changes in his life. Together they go for eternity, in other words for nothingness...